2015
DOI: 10.3831/kpi.2015.18.011
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Role of Capsaicin in Experimentallyinduced Lung Carcinogenesis

Abstract: Objectives:Capsaicin (CAP) is the chief pungent principle found in the hot red peppers and the chili peppers that have long been used as spices, food additives and drugs. This study investigated the anticancer potential of CAP through its ability to modify extracellular matrix components and proteases during mice lung carcinogenesis.Methods:Swiss albino mice were treated with benzo(a) pyrene (50 mg/kg body weight dissolved in olive oil) orally twice a week for four successive weeks to induce lung cancer at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Several studies found that activation of TRPV1 by capsaicin attenuated abnormal glucose homeostasis by increasing insulin secretion, insulin responses, and glucagon-like peptide 1 levels [ 19 , 20 , 21 ]. Furthermore, TRPV1 was shown as a regulator of growth factor signaling in the suppression of tumorigenesis [ 22 ], and its anti-cancer effect was also confirmed [ 23 , 24 , 25 ]. Furthermore, the TRPV1 receptor can be desensitized with high administration of capsaicin in nervous tissue [ 26 ], but whether this effect exists in cardiometabolic tissues was never tested.…”
Section: Physiological Function Of Trpv1mentioning
confidence: 99%
“…Several studies found that activation of TRPV1 by capsaicin attenuated abnormal glucose homeostasis by increasing insulin secretion, insulin responses, and glucagon-like peptide 1 levels [ 19 , 20 , 21 ]. Furthermore, TRPV1 was shown as a regulator of growth factor signaling in the suppression of tumorigenesis [ 22 ], and its anti-cancer effect was also confirmed [ 23 , 24 , 25 ]. Furthermore, the TRPV1 receptor can be desensitized with high administration of capsaicin in nervous tissue [ 26 ], but whether this effect exists in cardiometabolic tissues was never tested.…”
Section: Physiological Function Of Trpv1mentioning
confidence: 99%
“…Capsaicin‐induced apoptosis in human small cell lung cancer cells (NCI‐H82, NCI‐H69) was found to activate via the TRPV receptor and the calpain‐mediated pathways (Lau et al, ). Capsaicin played a chemo‐modulatory and anticancerous effects against Benzo[a]pyrene‐induced lung carcinogenesis in Swiss albino mice (Anandakumar et al, ).…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%
“…Capsaicin effects on prostate cancer using the transgenic adenocarcinoma of the mouse prostate (TRAMP) model was found to be chemopreventive [6], whereas it was also found to decrease prostate cancer cell proliferation and cell cycle progression through the inactivation of androgen receptor [7]. It was also found to modulate extracellular matrix components in an experimentally induced lung cancer model, suggesting it could also have an anti-tumor effect in lung cancer as well [8]. It was also shown to suppress the growth of leukemic cells via cell cycle arrest and apoptosis [9].…”
Section: Introductionmentioning
confidence: 97%